2017
DOI: 10.7860/jcdr/2017/24476.9360
|View full text |Cite
|
Sign up to set email alerts
|

Light Chain Myeloma induced Severe Hypertriglyceridemia

Abstract: Hyperlipidemia is very common in general population and incidence has further increased in recent years. Evaluation of patient presenting with lipid disorders is essential to obtain a definite diagnosis to prevent complications, and apply the most appropriate treatment. An isolated elevation in triglyceride levels may be caused by a primary disorder of lipid metabolism like familial hypertriglyceridemia. It may also arise secondary to a number of conditions like diabetes mellitus, alcohol intake, hypothyroidis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…To rule out other causes, we only include patients without any familial dyslipidemia or history of alcohol intake. As these two factors also play a role in increasing triglycerides as compared to polygenic etiologies like obesity, insulin resistance or diabetes mellitus [ 10 - 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…To rule out other causes, we only include patients without any familial dyslipidemia or history of alcohol intake. As these two factors also play a role in increasing triglycerides as compared to polygenic etiologies like obesity, insulin resistance or diabetes mellitus [ 10 - 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypertriglyceridemia is a manifestation of hyperlipidemia, and numerous studies have reported its association with an increased risk of multiple myeloma. Furthermore, evidence of high triglyceride levels has been observed in patients with multiple myeloma and benign monoclonal gammopathy ( 17 , 18 ). The precise mechanisms underlying the relationship between heightened triglyceride levels and multiple myeloma risk remain to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the emerging role of Lp(a) in the pathophysiology of inflammatory diseases, such as atherosclerosis, it should be noted that to date, no data exist on the role of Lp(a) in the development and progression of MM. Similarly, although hypertriglyceridemia has been reported in patients with hematological malignancies, such as acute promyelocytic leukemia ( 86 ), only few cases of patients with MM who developed hypertriglyceridemia have been reported, and its role in disease development remains unclear ( 87 , 88 ).…”
Section: Multiple Myeloma and The Lipoprotein Transport Systemmentioning
confidence: 99%